2016
DOI: 10.1523/jneurosci.1297-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Partitioning of Synaptic Vesicle Pools by the SNARE-Binding Protein Tomosyn

Abstract: Neural networks engaged in high-frequency activity rely on sustained synaptic vesicle recycling and coordinated recruitment from functionally distinct synaptic vesicle (SV) pools. However, the molecular pathways matching neural activity to SV dynamics and release requirements remain unclear. Here we identify unique roles of SNARE-binding Tomosyn1 (Tomo1) proteins as activity-dependent substrates that regulate dynamics of SV pool partitioning at rat hippocampal synapses. Our analysis is based on monitoring chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 109 publications
3
30
0
Order By: Relevance
“…elegans DCVs [21] as well as the direct interaction of rat tomosyn with the vesicular proteins Syt-1 [41] and Rab3 [29]. To differentiate between immobile synapses and mobile organelles, we performed live imaging of EYFP-tomosyn-m1 puncta and observed that many tomosyn-1 puncta moved along the neurite (typical example in Fig 3A–3C).…”
Section: Resultsmentioning
confidence: 99%
“…elegans DCVs [21] as well as the direct interaction of rat tomosyn with the vesicular proteins Syt-1 [41] and Rab3 [29]. To differentiate between immobile synapses and mobile organelles, we performed live imaging of EYFP-tomosyn-m1 puncta and observed that many tomosyn-1 puncta moved along the neurite (typical example in Fig 3A–3C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, comparison of WT and Rab27 KO lysates demonstrated no significant differences in synaptic protein expression levels, except for the V‐SNARE domain containing protein Tomosyn‐1. Tomosyn‐1, which is reported to act as a negative regulator on presynaptic release (Hatsuzawa, Lang, Fasshauer, Bruns, & Jahn, 2003; Yizhar et al., 2004), be subject to CDK5 phosphorylation and interact with Rab GTPases (Cazares et al., 2016), was reduced by approximately 62% (WT, 0.6259 ± 0.07; KO = 0.2389 ± 0.18).…”
Section: Resultsmentioning
confidence: 99%
“…One known effector of Rab3 is RIM1 which has been reported to form a trimeric complex containing Rab3 and Munc13 (Castillo et al., 2002; Schoch et al., 2002), a protein essential for exocytotic activity in mammalian glutaminergic neurons. The KO of Rab27B exhibited negligible effect on expression of the array of synaptic proteins that were assessed, with the exception of tomosyn‐1, a v‐SNARE containing protein that serves as a negative regulator of exocytosis (Hatsuzawa et al., 2003; Yizhar et al., 2004) and regulator of SV distribution between functionally defined resting and recycling SV pools in hippocampal neurons (Cazares et al., 2016). Tomosyn‐1 also serves as an effector of Rab3, and perhaps Rab27, GTPases in regulating SV pool dynamics (Cazares et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sro7p has also been reported to disrupt cell polarity via suppression of a small GTPase Rho3p (48). Similar to the yeast homolog, tomosyn has recently been shown to interact with the GTP-bound state of Rab3A to partition synaptic vesicle pools (49).…”
Section: Discussionmentioning
confidence: 99%